Semen reactive oxygen species levels are correlated with erectile function among chronic prostatitis/chronic pelvic pain syndrome patients. Issue 6 (November 2018) - Alkan, Ilter; Yüksel, Meral; Özveri, Hakan; Atalay, Anıl; Canat, Halil; Culha, Mehmet Gokhan; Arabacı, Çiğdem; Bozkurt, Muammer; Başar, Murad
Abstract Chronic Prostatitis/Chronic Pelvic Pain Syndrome (CP/CPPS) is often associated with erectile dysfunction (ED). However, the underlying pathophysiological mechanisms of ED occurrence are still unclear in patients with CP/CPPS. The aim of the study was to investigate superoxide anion (O2 − ) and total reactive oxygen species (ROS) production in semen of men with category IIIA CP/CPPS and their association with ED. This prospective study included 33 men with category IIIA CP/CPPS. Control group consisted of 13 healthy men. Total ROS and O2 − production were assayed by luminol and lucigenin-dependent chemiluminescence (CL) methods, respectively. ED was evaluated using the IIEF-5 questionnaire. Patients with CP/CPPS had significantly higher seminal total ROS and O2 − levels than healthy control subjects (2.9 ± 0.5 relative light unit (RLU) vs. 2.4 ± 0.2 RLU, p  < 0.001; luminol-dependent CL and 2.5 ± 0.4 RLU vs. 2.3 ± 0.2 RLU, p  = 0.02; lucigenin-dependent CL, respectively). Seminal O2 − and ROS levels were negatively correlated with IIEF-5 scores (r  = −0.556, r  = −0.536;p  < 0.001, respectively). These results may suggest O2 − /ROS overproduction could be one of the important mechanisms in the etiology of ED development in CP/CPPS patients.